Epidemiology of candidemia during COVID-19 pandemic era in a teaching hospital: A non-concurrent cohort study - Brandt, Flávio Pasa [UNESP]; Sawazaki, Jonas Atique [UNESP]; Cavalcante, Ricardo De Souza [UNESP] (Oxford University Press (OUP), 2024)
During the COVID-19 pandemic, an increase in the incidence of bloodstream infections caused by fungi of the Candida genus, also known as candidemia, was observed in patients with SARS-CoV-2 infection. This study aimed to assess the incidence of candidemia, the factors related to COVID-19-Associated candidemia (CAC), and prognostic factors. A non-concurrent cohort of 87 cases of patients aged over 18 years with candidemia between March 2020 and February 2022 was evaluated. Incidence density (ID) was calculated by the number of patient-days during the period. All causes of mortality within 30 days of observation were considered. Logistic regression and Cox proportional hazards regression were used, respectively, to determine factors associated with CAC and prognostic factors. Values <0.05 were considered significant. The ID of CAC was eight times higher than candidemia in patients without COVID-19 [2.40 per 1000 person-days vs. 0.27 per 1000 person-days; P <. 01]. The corticosteroid therapy was as an independent factor associated with CAC [OR = 15.98 (3.64-70.03), P <. 01], while abdominal surgery was associated with candidemia in patients without COVID-19 [OR = 0.09 (0.01-0.88), P =. 04]. Both patients with and without COVID-19 had a high 30 days-mortality rate (80.8% vs. 73.8%, respectively; P =. 59). Liver disease [HR = 3.36 (1.22-9.27); P =. 02] and the Charlson score [HR = 1.17 (1.01-1.34); P =. 03] were independent factors of death, while the use of antifungals [HR = 0.15 (0.07-0.33); P <. 01] and removal of the central venous catheter [HR = 0.26 (0.12-0.56); P <. 01] independently reduced the risk of death. These findings highlight the high incidence of candidemia in COVID-19 patients and its elevated mortality.
Keywords: candidemia; COVID-19; incidence; mortality